Polyethylenimine-Dermatan Sulfate Complex, a Bioactive Biomaterial with Unique Toxicity to CD146-Positive Cancer Cells - Kim, Bieong-Kil; Kim, Dongkyu; Kwak, Gijung; Yhee, Ji Young; Kwon, Ick-Chan; Kim, Sun Hwa; Yeo, Yoon (AMER CHEMICAL SOC, 2017)
We report unique bioactivity of a polycation-polyanion complex with potential utility for cancer therapy. A complex of disulfide-cross-linked polyethylenimine (CLPEI), a polycation used for gene complexation, and dermatan sulfate (DS), an anionic polysaccharide to shield excessive cationic charge of the former, has toxicity to a specific group of cancer cell lines, including B16-F10 murine melanoma, A375SM human melanoma, and PC-3 human prostate cancer cells. These CLPEI-DS-sensitive cells express CD146, which binds to the complex via interaction with DS. There is a positive correlation between toxicity and intracellular level of CLPEI, indicating that the CLPEI-DS-sensitivity is attributable to the increased cellular uptake of CLPEI mediated by the DS-CD146 interactions. In vitro studies show that CLPEI-DS complex causes G(0)/G(1) phase arrest and apoptotic cell death. In syngeneic and allograft models of B16-F10 melanoma, CLPEI-DS complex administered with a subtoxic level of doxorubicin potentiates the chemotherapeutic effect of the drug by loosening tumor tissues. Given the unique toxicity, CLPEI-DS complex may be a useful carrier of gene or chemotherapeutics for the therapy of CD146-positive cancers.
Keywords: CD146; EXPRESSION; DELIVERY; CHITOSAN; PROGRESSION; MOLECULE; ADHESION; CARRIERS; LIPIDS; DEATH